Peran Guru Kelas dalam Meningkatkan Minat Belajar Siswa Kelas IV di MI Nawwarul Uyun NW Serumbung Kecamatan Jerowaru: The Role of Class Teachers in Increasing the Learning Interest of Grade IV Students at MI Nawwarul Uyun NW Serumbung, Jerowaru District - Zakaki (Al-Faiza : Journal of Islamic Education Studies, 2025)
School is a formal educational environment for children. Schools function to shape students into whole individuals. Where teachers in schools play a role in educating, teaching and facilitating their students until learning objectives are achieved. The study aims to determine the role of class teachers in increasing students' interest in learning at MI Nawwarul Uyun NW Serumbung and to determine how to overcome the obstacles of class teachers in increasing the interest in learning of class IV students at MI Nawwarul Uyun NW Serumbung. This type of research uses a descriptive qualitative approach. Data collection techniques using interviews, observations, and documentation with the research subjects being the principal, teachers, and students. The results of this study indicate that the interest in learning of class IV students at MI Nawwarul Uyun NW Serumbung can be seen from the efforts made by class teachers to increase students' interest in learning. The data analysis technique uses data triangulation, data reduction (data reduction), data presentation (data presentation), and concluding (drawing conclusions). Based on the results of the analysis and discussion, it can be concluded that the Role of Class Teachers in Increasing Students' Interest in Learning is categorized as not optimal. The implementation of activities to increase students' interest in learning is: Teachers as Educators, Teachers as Facilitators, Teachers as Leaders, Teachers as Mentors, Teachers as Motivators, Teachers as Evaluators, and Teachers as Assessments. Class Teachers' Obstacles in Increasing Students' Interest in Learning. Teachers also have obstacles, namely: Lack of Facilities, Lack of Parental Support and Participation, and Lack of Student Interest in Learning.